Global estimates of service coverage for severe mental disorders: findings from the WHO Mental Health Atlas 2017 - Kara Jaeschke; Fahmy Hanna; Suhailah Ali; Neerja Chowdhary; Tarun Dua; Fiona Charlson (Cambridge Prisms: Global Mental Health, 2021)
Abstract Background The study estimated service coverage for severe mental disorders (psychosis, bipolar disorder and moderate-severe depression), globally and regionally, using data collected from the Mental Health Atlas 2017.